Compression force promotes the osteogenic differentiation of periodontal ligament stem cells by regulating NAT10-mediated ac4C modification of BMP2 - Yan Feng; Ting Zhang; Yue Chang (Journal of Orthopaedic Surgery and Research)
Abstract Background Orthodontic treatment applies specific corrective forces to teeth, transmitting stress to periodontal tissue, thereby regulating the growth and development of periodontal ligament stem cells (PDLSCs). Recently, N-acetyltransferase 10 (NAT10) mediated N4-acetylcytidine (ac4C) modification is demonstrated to play a key role in the osteogenic differentiation of stem cells. Therefore, this study aimed explore the effects of Orthodontic treatment on the NAT10 mediated ac4C modification and osteogenic differentiation of PDLSCs. Methods Compressive force was used to treat PDLSCs to simulate orthodontic force treatment. The ALP and ARS staining was performed to analyze the osteogenic differentiation of PDLSCs. Besides, ac4C dot blot and ac4C-RIP assays were performed to detect the global ac4C levels and BMP2 ac4C levels. The relationship between NAT10 and BMP2 was confirmed by RIP assay and immunofluorescence staining. The mRNA and protein levels of RUNX2, Oxterix and BMP2 were detected by RT-qPCR and western blot assays. Results Compressive force treatment promoted the osteogenic differentiation of PDLSCs, and enhanced the global ac4C levels and NAT10 levels in PDLSCs. NAT10 overexpression further promoted the osteogenic differentiation of compressive force treated PDLSCs. Besides, NAT10 overexpression increased ac4C levels of BMP2 and enhanced the mRNA stability of BMP2. Remodelin treatment significantly decreased the ac4C and mRNA levels of BMP2. Furthermore, BMP2 silencing reversed the role of NAT10 in the compressive force treated PDLSCs. Conclusion This study demonstrated that compressive force promotes cell viability and osteogenic differentiation of PDLSCs by regulating BMP2 levels mediated by NAT10. NAT10 mediated ac4C levels of BMP2 is the key signaling axis of orthodontic stress in promoting cell growth and osteogenic differentiation of PDLSCs. Graphical abstract